PENGEMBANGAN SISTEM RESERVASI VALET OTTO PARKING MENGGUNAKAN FRAMEWORK LARAVEL, NEXT.JS, DAN FLUTTER DENGAN METODE AGILE KANBAN DI PT NUSANTARA INFRASTRUCTURE TBK - Kevin Leonard Sugiman (2023)
The parking business has become a common thing in all regions of Indonesia. As technology develops massively, many businesses are experiencing changes. Likewise with the parking business, many companies are starting to switch from conventional parking systems to being fully digitized. Conventional parking systems have several problems, including conventional parking systems cannot notify parking users before the parking users come to the parking location, this makes many parking users come to the parking lot without knowing that the parking lot is full, so users must find a place another parking nearby. In addition, the conventional parking report system that has not been integrated with other branch parking lots makes the parking report process more difficult for the parking manager to manage. Departing from experience in the Toll Road business company PT Nusantara Infrastructure Tbk in terms of the toll payment system handled by the Internal IT Team without using a third party, where the system is very similar to the existing parking payment system. In this study the authors used the agile kanban method in the software development process, the authors also used the Laravel framework for backend application development, Next.js and Flutter frameworks for frontend application development, and MySQL as a database management system. It is hoped that this parking system can provide convenience to parking in finding the closest parking location to the user, seeing the number of available parking users, and making parking reservations. In addition, it is hoped that this system can also provide convenience to parking managers in integrating parking branches owned by parking managers and make it easier for parking managers to obtain parking reports for each parking branch owned.